Microbial ecology of stable flies: Effect of bacterial community of aging horse manure on stable fly oviposition and larval development - Albuquerque, Thais Aguiar De; Zurek, Ludek (My University, 2012)
Stable flies (SF) are blood-sucking insects with great negative impact on livestock. SF larvae develop primarily in animal manure. Our hypothesis was that the microbial community in animal manure changes over time and plays an important role in SF oviposition and development. Two-choice bioassays were conducted using 2- week old horse manure (standard) and aging horse manure (fresh to 5 weeks old) to evaluate the effect of manure age on SF oviposition and larval development. Results showed that fresh manure is not attractive for SF oviposition and that the attractiveness increases as manure ages but declines from 4 weeks of age. Eggs artificially deposited on 1, 2 and 3 weeks old manure resulted in significantly higher SF survival comparing to that of fresh, 4, and 5 week old manure. The bacterial community of horse manure was analyzed by 454- pyrosequencing. The microbial structure shifted from strict anaerobes (Clostridium, Eubacterium, Bacteroides, Ruminococcus) in fresh manure to facultative anaerobes/aerobes (Bacillus, Stenotrophomonas, Brevundimonas, Sphingomonas, and Pseudomonas) in 1-4 week old manure. In conclusion, the microbial community in 2-3 weeks old horse manure is the most attractive for SF oviposition and provides the suitable habitat for SF development. Manure of this age should be the main target for disrupting SF life cycle to manage SF around livestock. Better understanding of SF microbial ecology is critical for development of novel SF management strategies that could be based on alteration of the microbial community of SF habitat to generate a substrate non-conducive to fly oviposition and/or larval development
Keywords: Stomoxys calcitrans; stable fly; oviposition; development; bacteria; horse manure